Programming in C# : Learn Basic to Advanced Concepts of C#, Including C# 8, to Pass Microsoft MCSD 70-483 Exam. - Bhalla, Simaranjit Singh (Packt Publishing, Limited, 2019)
This book is a certification guide to prepare you for the skills that you need to pass the exam and build an acumen of problem-solving with C#. The book will be designed as preparation material for the Microsoft specialization exam in C#.